Legal Framework of Pesantren Islamic Finance for Grassroots Economic Empowerment - Hana Al Ithriyah; Razak, Akhmad Zakki Abd.; Yani, Ahmad (Faculty of Sharia and Islamic Economic, Universtas Annuqayah, 2025)
Despite Indonesia’s Islamic finance growth reaching IDR 2,207 trillion, grassroots communities face systematic exclusion due to stringent collateral requirements and procedural complexity imposed by formal financial institutions. This study examines how UJKS Annuqayah navigates legal-regulatory frameworks and Shariah compliance while implementing trust-based mechanisms for grassroots financial inclusion. This research methodology is a qualitative case study was conducted through in-depth interviews (22 participants), participant observation (50 sessions), and document analysis (127 documents) at UJKS Annuqayah, Sumenep, Indonesia, from May-October 2024. The result is UJKS Annuqayah achieves zero default rates through trust-based collateral leveraging social capital and daily collection systems (setoran harian), enabling financing without physical assets while maintaining DSN-MUI Fatwa No. 04/2000 compliance. However, modest income impacts (8-15% growth) and sustainability pressures (IDR 25-30 million annual deficit) constrain transformative potential. The conclusion and recommendations: Pesantren-based institutions offer viable Islamic microfinance models balancing Shariah principles and accessibility. Future research should conduct comparative multi-case studies and longitudinal impact assessments. Research Implications: The study advances maqasid al-Shariah application in microfinance and reconceptualizes collateral through social capital theory. Managerial Implications: Policymakers should develop proportionate regulatory frameworks recognizing alternative risk mitigation, while practitioners should align payment structures with grassroots cash flow patterns.